Association between sleep quality with maternal and neonatal outcomes during the covid-19 pandemic - Maryam Akbari; Sara EsmaeilzadehSaeieh; Malihe Farid; Arman Shafiee; Mahmood Bakhtiyari; Touran Bahrami Babaheidari; Mansoureh Yazdkhasti (BMC, 2024)
Abstract Aim Sleep disorders during pregnancy can impact maternal and neonatal outcomes. The objective of this study is to examine the relationship between sleep quality and maternal and neonatal outcomes during the COVID-19 pandemic. Method This prospective cohort study was conducted at the Educational-Therapeutic Center of Shohadaye Yaftabad Referral Hospital in Tehran, Iran, from December 2020 to September 2022. A total of 198 eligible participants were randomly assigned to either the sleep disorders group or the no sleep disorders group. Data were collected through demographic questionnaires, the Corona Disease Anxiety Scale (CDAS) questionnaire, the Pittsburgh Sleep Quality Index (PSQI), and the checklist for maternal and neonatal outcomes. Results At baseline, the sleep disorders and no sleep disorders groups were similar in terms of age, body mass index (before pregnancy), education level, employment status, gravida, parity, abortion, and history of COVID-19. Within the sleep disorders group, there was a statistically significant, direct linear correlation between sleep disorders and FBS 34-36 weeks (r = 0.33, P < 0.001) as well as Corona Disease Anxiety (CDA) (r = 0.35, P < 0.001). The linear regression results indicated that for every unit increase in sleep disorders, the risk of FBS 34-36 weeks increased by 1.09 times (β = 1.09, P < 0.001). Additionally, sleep disorders increased the risk of CDA by 1.36 times (β = 1.36, P < 0.001). The results showed no statistically significant differences in terms of birth weight, type of delivery (vaginal or cesarean section), gestational age (preterm or full term), length of labor stages (first and second stage), Apgar score at minutes 1 and 5, and NICU admission between the two groups. Conclusion Based on the results, a certain degree of correlation exists between sleep quality and FBS at 34-36 weeks and CDA. These findings underscore the need for future public health guidelines to formulate detailed strategies to improve sleep quality during the COVID-19 pandemic.